Střednědobé výsledky léčení nestabilních skluzů proximální epifýzy femuru zavřenou repozicí - Chomiak, J; Ošťádal, M; Dungl, P (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: The study aimed to evaluate the results of closed reduction and epiphyseodesis of unstable slips of the proximal femoral epiphysis. The hypothesis was that the clinical and radiological results of this method and incidence of avascular necrosis are comparable to the results of closed reduction and open reduction using surgical hip dislocation reported by literature. MATERIAL AND METHODS: In the period 2013-2023, 20 patients were treated for unstable slips in one institution. Whereas the boys were older (mean age of 13.4 years) than girls (mean age of 11.6 years), the gender distribution was equal. Acute on chronic slips prevailed over the acute slips (ratio 3:1). The slips were treated using the closed reduction, transphyseal fixation and capsular decompression at 6 to 240 hours after slip (81 hours on average). All patients were treated concurrently on the contralateral side as the prevention of the slip or to treat the grade I slips (two patients). The follow-up ranged from 7 months to 7 years. Clinical results were evaluated according to two scores: 1) own score (Bulovka University Hopspital score) based on the reduction of ROM, shortening of extremity and limitations of activities; 2) D'Aubigne-Postel score. In the radiological evaluation, correction of slip angle, alpha-angle, avascular necrosis (AVN) and the prominence of the anterior margin of the femoral neck on axial radiographs were evaluated. RESULTS: According to the Bulovka University Hospital score, there were 10 excellent results (50%) with no limitation of activity, including sport, in tree cases the results were very good (15%) and in five cases good (25%), respectively, with some limitation of activity, and two results were unsatisfactory (10%) with severe limitation of activity due to the AVN. According to the D'Aubigne-Postel score, there were 14 excellent results (70%), four good results (20%), and two unsatisfactory results (10%). The slip reduction was as follows: under 20 deg. in five patients; under 30 deg. in 10 patients, and over 30 deg. in five patients, respectively. Alfa-angle was greater than 63 degrees (range 45-88 deg.) on average. Prominence of the off-set epiphysis-femoral neck and femoroacetabular impingement (FAI) were observed in six patients. Remodelling of this prominence was seen in one patient four years after surgery. Shortening of the femoral neck over 1 cm was reported in two patients. Complete AVN with severe deformity of the hip was noted in two patients. DISCUSSION: Our hypothesis was confirmed because the results of treatment of the unstable slips by closed reduction are comparable with the published results of the same method and with surgical hip dislocation. The results correspond with those of large published cohorts of patients concerning the correction as well as rate of complications. CONCLUSIONS: According to our results, urgent gentle closed reduction, transphyseal fixation and capsular decompression represent efficient and relatively safe methods of treatment of unstable slips with low incidence of complication. Residual deformity of the off-set epiphysis-femoral neck and FAI represent limitations of this method. KEY WORDS: slipped proximal femoral epiphysis, unstable slips, closed reduction, transphyseal fixation.
Keywords: skluz proximální femorální epifýzy; Adolescent; Child; Range of Motion, Articular; lidé; Female; rozsah kloubních pohybů; mužské pohlaví; nekróza hlavice femuru; Femur Head Necrosis; Male; dítě; Slipped Capital Femoral Epiphyses; mladiství; Treatment Outcome; výsledek terapie; ženské pohlaví; Humans